The Covid-19 pandemic and its effects on well-being among university staff in Malaysia - D’Silva, Jeffrey Lawrence; Ismail, Ismi Arif; Mohamed Shaffril, Hayrol Azril; Kamarudin, Nurul Akhtar; Dahalan, Dzuhailmi (Human Resource Management Academic Research Society, 2021)
Well-being among employees at different organizations had been greatly disrupted during the Covid-19 pandemic especially adapting working in a different setting leading to stress, depression, and work exhaustion. Till today there is little empirical studies carried out to determine the level of well-being among university employees. Thus, this study investigated the level of well-being among the university staff attached to a university in Malaysia. The survey instrument was developed using past literature. The final respondents for this study were 947 and it was obtained using the online platform. Overall, the findings showed that the well-being index stood at 74.16 indicating generally the staff are having a moderate well-being working in the university. The study suggests that to further enhance well-being among university staff emphasis should be placed to improve on career development, work load and governance.